Secondhand Smoke in Pennsylvania Casinos: A Study of Nonsmokers' Exposure, Dose, and Risk - Repace, James L. (American Public Health Association, 2009)
Objectives. I assessed air pollution, ventilation, and nonsmokers' risk from secondhand smoke (SHS) in Pennsylvania casinos exempted from a statewide smoke-free workplace law. Methods. I measured respirable suspended particles (RSPs), particulate polycyclic aromatic hydrocarbons (PPAHs), and carbon dioxide inside and outside casinos; measured changes in patrons' urine cotinine after casino visits; and assessed SHS impact on workers and patrons, using exposure–response models, air quality standards, and odor and irritation thresholds. Results. PPAH and RSP concentrations in casinos were, on average, 4 and 6 times, respectively, that of outdoor levels despite generous ventilation and low smoking prevalence. SHS infiltrated into nonsmoking gaming areas. Patrons' urine cotinine increased 1.9 ng/mL on average after about 4-hour visits. Conclusions. SHS-induced heart disease and lung cancer will cause an estimated 6 Pennsylvania casino workers' deaths annually per 10 000 at risk, 5-fold the death rate from Pennsylvania mining disasters. Casinos should not be exempt from smoke-free workplace laws.